مەترسییە ژینگەییەکانى راماڵینى ئاویى لە قەزاى شارباژێڕ - ئەمین, پ.ی. د هاوڕێ یاسین محمد; علی, م.هاودین کامل (Sulaimani Journal for Humanities, 2023)
The study area is Sharbazher district, which is considered one of the regions of Sulaymaniyah Governorate and is located in the eastern part of the province and the Kurdistan Region of Iraq. The study analyzed the environmental risks of water erosion in the region, based on the characteristics of the nature of the district. Based on the analysis method (descriptive and quantitative analysis), analysis and comparison methods were followed, field surveys were conducted in the study area on several different dates, data were collected and scenes were monitored. Through some equations strength, magnitude, and amount of water erosion is shown. Based on the Fournier equation, the magnitude of splash erosion was (106.6), in the coefficient of variation for measuring splash erosion using the standard deviation equation showed that the level of erosion during the months (November to March) was in the class of strong erosion (more than 0.65). The magnitude of erosion based on the Douglas equation (5.1m3/km2/year) and (90.2%) of the study area the degrees of follise erosion is in a high to sever levels of erosion based on the Bergsma classification. The research used the ES equation of (FAO) organization. The (ES) equation depends on the analytical indexes of Fournier equation, the soil density value, topography value and the utilization type of the area of study. The research yielded that the amount of water erosion in the area of study was (7.4 tons/acre/year), and the thickness of the water erosion was (2.1 erosion/mm/year). The study concluded that in the area of study, the amount of rainfall primarily and the characteristics of low and high surfaces, especially steep surfaces, soil density and land cover successively affected the strength, size and amount of water erosion.
Keywords: Environmental threats; Water Erosion; Erosion (ES); Sharbazher district